Efficacy of bolus injections of landiolol hydrochloride as premedication in coronary artery CT angiography - Mark Barwig; Michael Janisch; Johannes Gessl; Wolfgang Kübler; Christopher König; Gerold Schwantzer; Helmut Schöllnast (Insights into Imaging)
Abstract Purpose To assess the efficacy of bolus injections of landiolol hydrochloride as premedication in coronary artery CT angiography (CCTA). Methods The study population consisted of 37 patients (17 female; median age, 56 years; IQR, 19 years; range, 19–88 years) who underwent CCTA after intravenous injection of landiolol hydrochloride due to a heart rate > 60 bpm. Landiolol hydrochloride was administered in a stepwise manner until a heart rate of ≤ 60 bpm was achieved or a maximum dose of 60 mg was reached after six injections. Heart rates routinely displayed continuously on the CT scanner before the start of the landiolol hydrochloride injection (HRPRE), after each partial dose (HR1–6), during the CT scan (HRCT), and after the examination before moving from the CT table (HRPOST) were recorded. Furthermore, the blood pressure routinely measured before (BPPRE) and after the examination before moving from the CT table (BPPOST) was recorded. Results A HRCT of ≤ 60 bpm was achieved in 13 patients (35%) and a HRCT ≤ 65 bpm was achieved in 25 patients (68%). The mean difference (± SD) between HRPRE and HRCT was −11 ± 9 bpm in total, −14 ± 10 bpm in patients without oral beta-blocker premedication and −6 ± 5 bpm in patients with oral Beta-blocker premedication. Conclusions Landiolol hydrochloride enables a reduction of the heart rate in patients with and without oral beta-blocker premedication, whereby the use of serial partial doses is a simple and effective approach in clinical routine. Critical relevance statement In cardiac CT, weight-independent, stepwise landiolol hydrochloride injection up to 40 mg reduces heart rate by −14 bpm without and −5 bpm with oral beta-blocker premedication, and achieves heart rates of ≤ 65 bpm in a significant proportion of patients. Key Points The ideal heart rate for cardiac CT is ≤ 60–65 bpm, which improves image quality and reduces radiation dose. In cardiac CT, landiolol hydrochloride intravenously reduces heart rate by −14 bpm. Heart rate of ≤ 65 bpm can be achieved in a significant proportion of patients. Graphical Abstract